(untitled) (Journal of the College of Basic Education, 2022)
Aims to present research to identify the effectiveness of the document program to psychodrama in breaking the common behavioral habits in children , autism, consisted research community (474) children and a child autism, and adopted the researchers on the intentional sample consisted of (6) A child autism for the application of the program. The researchers built a common behavioral habits measure in children , autism yen document to Jthrey theory according to the steps of scientific procedures and then verify psychometric his properties, then built a document program to psychodrama to break the behavioral habits ALACHUA Iah in children autism yen document it to the theory of autism, then The scale and program were applied and the results were as follows: 1 - The children of the self - research sample suffer from common behavioral disorders . 2 - independent variable (training program based on the psychodrama) a clear impact on the dependent variable (behavioral habits) as test results and trailed Cookson for atest Indication of differences before and after application of the program. Theindependent variable (training program based on the psychodrama) and clear the effectiveness of the dependent variable (behavioral habits) as Mac Jojian test trailed results for a test Indication of differences in post - test and delay. Al-Bahathan reached conclusions, recommendations and proposals .